2018
DOI: 10.1016/j.ijpharm.2018.09.040
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of HBEC-5i endothelial cell line cultivated in astrocyte conditioned medium as a human blood-brain barrier model for ABC drug transport studies

Abstract: Endothelial cells are main components of the Blood-Brain Barrier (BBB) and form a tight monolayer that regulates the passage of molecules, with the ATP-Binding Cassette (ABC) transporters efflux pumps. We have developed a human in vitro model of HBEC-5i endothelial cells cultivated alone or with human astrocytes conditioned medium on insert. HBEC-5i cells showed a tight monolayer within 14 days, expressing ZO-1 and claudin 5, a low apparent permeability to small molecules, with a TEER stability during five day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 40 publications
0
34
3
Order By: Relevance
“…Astrocytes are the most abundant cell type within the CNS, and they provide structural support, promote the formation of the BBB, and release beneficial factors that maintain brain cell development and homeostasis of the extracellular environment [24]. The function of brain endothelial monolayer cells, ATP-binding cassette transporters, and TJP expression for example, is enhanced when the cells are co-cultured with astrocytes or ACM for a period of time [5, 25]. In the present study, ACM did not alter TJP expression or the integrity of bEnd.3 cell monolayer, potentially due to the relatively short culture period, which was consistent with the results from previous studies [11, 25].…”
Section: Discussionmentioning
confidence: 99%
“…Astrocytes are the most abundant cell type within the CNS, and they provide structural support, promote the formation of the BBB, and release beneficial factors that maintain brain cell development and homeostasis of the extracellular environment [24]. The function of brain endothelial monolayer cells, ATP-binding cassette transporters, and TJP expression for example, is enhanced when the cells are co-cultured with astrocytes or ACM for a period of time [5, 25]. In the present study, ACM did not alter TJP expression or the integrity of bEnd.3 cell monolayer, potentially due to the relatively short culture period, which was consistent with the results from previous studies [11, 25].…”
Section: Discussionmentioning
confidence: 99%
“…The model was composed of HBEC-5i endothelial cells (from ATCC-Manassas, VA, USA) cultivated with conditioned medium from human astrocytes(HA from ScienCell Research Laboratories, Carlsbad, CA, USA) as previously described (Puech et al, 2018b).Cells were cultured in DMEM-F12 HAM, supplemented with 10% FBS and 1% antibiotic antimycotic solution. Cells were maintained in a humidified incubator at 5% CO2 and 37°C.…”
Section: Hbec-5i Bbb Culturementioning
confidence: 99%
“…This study was conducted on an in vitro model of culture of cerebral endothelial cells in conditioned media. This model could be improved with astrocytes and pericytes; nevertheless, it has been shown earlier that it is a good pharmacological model 15 . Our work showed that our model may screen patient serum and may be an interesting tool to evaluate risk and may be, one day, the reversal effects in sleep apnea patients.…”
Section: Discussionmentioning
confidence: 99%
“…The BBB model was composed of HBEC-5i endothelial cells and was cultivated with human astrocyte conditioned medium on insert as previously described 15 . All cells were cultured in DMEM-F12 HAM and used before passage number 20, which is the time where these cells may begin to lose their BBB properties.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation